2022
DOI: 10.3390/life12111699
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT for Breast Cancer Diagnosis

Abstract: Background: We report the results of our retrospective analysis of the ability of standard chest CT scans to correctly diagnose cancer in the breast. Methods: Four hundred and fifty-three consecutive women with chest CT scans (contrast and non-contrast) preceding mammograms within one year comprise the study population. All chest CT images were reviewed by an experienced fellowship-trained chest radiologist and mammograms by an experienced fellowship-trained mammographer without the benefit of prior or ancilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Interestingly, our patient’s CT scan report did not detect the presence of any underlying breast tumor, even on retrospective review. While existing guidelines do not recommend the use of CT scans for breast cancer screening due to scant evidence of benefit and higher radiation exposure, there is some evidence that CT scans with cuts as fine as 1.25mm may be comparable to mammography in sensitivity ( 11 , 12 ). For our patient, breast cancer may have gone undetected on CT scan because the slice thickness was 3mm, possibly causing a 6 × 10 × 6mm lesion to appear small and non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our patient’s CT scan report did not detect the presence of any underlying breast tumor, even on retrospective review. While existing guidelines do not recommend the use of CT scans for breast cancer screening due to scant evidence of benefit and higher radiation exposure, there is some evidence that CT scans with cuts as fine as 1.25mm may be comparable to mammography in sensitivity ( 11 , 12 ). For our patient, breast cancer may have gone undetected on CT scan because the slice thickness was 3mm, possibly causing a 6 × 10 × 6mm lesion to appear small and non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…High breast density can be reliably diagnosed on chest CT [ 37 , 38 ]. Retrospective research has demonstrated that three-dimensional chest CT is sensitive and specific for breast cancer diagnosis [ 39 , 40 ]. Future prospective studies are necessary to evaluate a possible role of chest CT in breast cancer diagnosis.…”
Section: Current Imaging Practices For Breast Cancer Screening Monito...mentioning
confidence: 99%
“…Our previous research identified breast masses on chest CT in 44 of 453 women (9.7%) ( 4 ). Benign breast masses were more likely to be small in size and have low Hounsfield units (HUs) and smooth borders; cancer was more likely to be large in size, contain high HU, and less likely to have a smooth border ( 4 ). The measurement of HU on CT was helpful for identifying cystic lesions.…”
Section: Introductionmentioning
confidence: 99%